O processo de aprendizagem organizacional: perspectivas do poder judiciário - Souza, Marcia Relvas de (2012)
Organizational learning has emerged as a relevant issue in organizational studies. This study aimed to identify, from the perception of managers responsible for people or knowledge management, in which way judicial organizations implement practices that can facilitate the process of organizational learning. The theoretical basis was developed from the theories about organizational learning, knowledge and skills. The research is characterized as qualitative and descriptive and the data was collected through literature review and field research. The option for the field research was the semi-structured interviews, carried out with managers of four different courts, states and federal regional. The data analysis shows that judicial organizations are implementing actions related to organizational learning, but there is still a great challenge in empowering them in search of a collective growth. Moreover, it showed the importance of coordination of these actions and context that helps the learning process. However, the survey revealed that some factors may inhibit this process. Investments and effort to implement practices and technologies are noticed, as well as an enthusiasm and the conclusion by the managers that the Judiciary had a breakthrough in latest years.